STRATEGI BAURAN PROMOSI DALAM MEMPERTAHANKAN EKSISTENSI JASA TRANSPORTASI TAKSI BLUE BIRD DI PEKANBARU - Nadya Salma Shafira; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The entry of online taxi to Pekanbaru has made Blue Bird Group Pekanbaru make a change from conventional taxis to online taxis and do promotional activities as a strategy to maintain the existence. The purpose of this study was to determine the strategy in maintaining the existence of the company and to determine the promotion mix strategy in maintaining the existence of Blue Bird taxi transportation services in Pekanbaru. This study used a qualitative descriptive method with data collection techniques, interviews, unstructured observation, and documentation. The research subjects used purposive sampling technique. The data analysis technique used in this research was the interactive model of Miles and Huberman and the data validity technique used was the extension of participation and triangulation.The result found that Blue Bird Group Pekanbaru has made a strategy to maintain existence of collaborating with Gojek which launched GoBlueBird and GoCar service also launched My Blue Bird online taxi. Blue Bird Group Pekanbaru also did some promotional mix activities are include advertising promotion, sales promotion activities, internet marketing activities, and event marketing activities to defend the existence of the Blue Bird Group Pekanbaru. Keywords: Strategy, Promotion mix, Existence, Blue Bird